Ultra-high compressive strength of 3D woven spacer composites with bulked glass fiber and saturated resin absorption. (15th June 2022) - Wang, Liyong; Chen, Long; Li, Wuzhou; Zheng, Liangang; Qiu, Yiping; Xu, Fujun
Abstract: Three-dimensional woven spacer composites (3DWSCs) have a great potential to applied in aerospace or transportation fields due to their high strength-to-weight and stiffness-to-weight ratios, with excellent skin-core debonding resistance. Among these properties, the compressive strength of the 3DWSCs which is most critical, and still needs to be improved to meet the highly requirements in practical applications. In this study, we designed and manufactured 3DWSCs with highly enhanced compressive strength and energy absorption by adopting bulked glass fibers (BGFs) as pile yarns to weave its core layer to absorb more epoxy resin. Consequently, the specific compressive strength of 3DWSCs woven by BGFs as pile yarns with saturated epoxy resin absorption was 52.54 MPa g −1 cm 3, 180% higher than that of the 3DWSCs woven by regular glass fiber (RGFs). Furthermore, the work of fracture of 3DWSCs woven by BGFs as pile yarns with saturated epoxy resin absorption was 14.82 N m, which enhanced 474% compared with that of 3DWSCs woven by RGFs. The failure cross sections depicted multiple brittle fractures of the pile yarns for both composites under compression, which caused multiple peaks in their stress–strain curves.